2005 IEEE Pulsed Power Conference 2005
DOI: 10.1109/ppc.2005.300539
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Charge Conduction and Self-Breakdown in Transformer Oil

Abstract: pact pulsed power and switching systems. An insulating fluid such as transformer oil is a critical component in With a fast coaxial setup using a needle/plane geometry high voltage and pulsed power systems. The desire for and a high sensitivity electrometer, conduction mecha-compact pulsed power systems drives research to develop nisms in transformer oil at varying temperature and hy-a model that is capable of describing the basic processes drostatic pressure are quantified. There are 3 stages in the of liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
(5 reference statements)
1
4
0
Order By: Relevance
“…In both cases (Figures 8 and 10), the anode characteristics control the mechanism of the same injection barrier height on the two electrodes. This result is the same as that of Butcher et al, 9 who also found that for a plane/plane system under the same conditions, the anode characteristics control the mechanism. This proves that the realized program reproduces correctly charge transport in a dielectric under intense electric field.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…In both cases (Figures 8 and 10), the anode characteristics control the mechanism of the same injection barrier height on the two electrodes. This result is the same as that of Butcher et al, 9 who also found that for a plane/plane system under the same conditions, the anode characteristics control the mechanism. This proves that the realized program reproduces correctly charge transport in a dielectric under intense electric field.…”
Section: Resultssupporting
confidence: 90%
“…• For injection barrier heights at the cathode greater than or equal to injection barrier heights at the anode, Φ 0− ≥ Φ 0+ , the mechanism is controlled by the anode characteristics. 9 The charge density is important at the anode. • For Φ 0− < Φ 0+ , the charge density is higher at the cathode, and the mechanism is controlled by the cathode characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations